Reseña de: Commentary to Tatiana Seijas’ review of The Atlantic World and the Manila Galleons: Circulation, Market, and Consumption of Asian Goods in the Spanish Empire - Gasch Tomás, José Luis (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2021)
El presente texto es un comentario y réplica a la reseña escrita por Tatiana Seijas en New West Indian Guide (94, 2020) asobre el libro de José L. Gasch-Tomás titulado The Atlantic World and the Manila Galleons: Circulation, Market, and Consumption of Asian Goods in the Spanish Empire (Leiden, the Netherlands: Brill, 2019. 258 pp.).